Great Pajama Jobs - Hannon, Kerry (Ascent Audio, 2020)
In 2020, the workplace has been transformed and working from home has exploded. It may, in fact, be the new reality of working for many of us, some full-time, some as a hybrid work scenario. With some information and expert guidance, you can transform your workday, take control of your time, and explore exciting new opportunities. Great Pajama Jobs is your playbook. Until recently, you may have gone to an office that was uninspiring or chaotic, or spent a large part of your busy day responding to emails and working on computer-tasks that could easily be accomplished from home. You may have spent hours commuting each day. Then too, you may be a military spouse in search of an ideal remote job to take with you to a new base, or you may need to manage your personal health issues or caregiving duties. Or you may simply want to inch a little closer to a more favorable work-life balance. The truth is, you may need the autonomy and flexibility of working remotely for a myriad of reasons. Great Pajama Jobs is your ultimate guide to finding a job where you can work remotely and advance your career while working in pajamas (or certainly something more comfortable than traditional work garb).